The water heat pump operation under frost conditions on the evaporator surface - V. I. Maksimov; A. Saloum (Известия высших учебных заведений: Проблемы энергетики)
The conditions and characteristics of ice formation on the pipe surface of a heat pump evaporator which depends on water ( at a temperature lower than 280 K) as a low-grade energy source are investigated experimentally. Under the operating conditions of this heat pump, the ice thicknesses and temperatures values at freon pipe wall and for water in the evaporator are registered. The results allowed us to make a conclusion of the possibility to use a water source heat pump in practical applications under the conditions of partial ice coverage for the evaporator surface to heat up water in a condenser to 313 K. It is established from experiments that with the decrease in water initial temperature in the evaporator by 6 degrees, the maximum value of formed ice thickness on the evaporator surface is increased by 30 %. The dependence of Nusselt number on the natural convection characteristics undergoing phase change is established.